2018
DOI: 10.5194/bg-15-2289-2018
|View full text |Cite
|
Sign up to set email alerts
|

Particulate barium tracing of significant mesopelagic carbon remineralisation in the North Atlantic

Abstract: Abstract. The remineralisation of sinking particles by prokaryotic heterotrophic activity is important for controlling oceanic carbon sequestration. Here, we report mesopelagic particulate organic carbon (POC) remineralisation fluxes in the North Atlantic along the GEOTRACES-GA01 section (GEOVIDE cruise; May–June 2014) using the particulate biogenic barium (excess barium; Baxs) proxy. Important mesopelagic (100–1000 m) Baxs differences were observed along the transect depending on the intensity of past blooms,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(69 citation statements)
references
References 74 publications
5
63
0
Order By: Relevance
“…In our study region, 5 diatoms dominate the phytoplankton communities at the early stage of the spring bloom (Brown et al, 2003), and are an important producer of biogenic silica (bSiO 2 ) (Nelson et al, 1995) which is the main carrier for scavenged Al (Moran and Moore, 1988b;Stoffyn, 1979). Elevated bSiO 2 concentrations and associated high export rates of bSiO 2 were measured in the ENAB (up to 1.19 µM BSi) and in the IrB and LB (up to 4.27 and 4.63 µM bSiO 2 respectively) (Lemaitre et al, 2017). .…”
Section: Remineralization Versus Scavenging In the North Atlantic Andmentioning
confidence: 88%
“…In our study region, 5 diatoms dominate the phytoplankton communities at the early stage of the spring bloom (Brown et al, 2003), and are an important producer of biogenic silica (bSiO 2 ) (Nelson et al, 1995) which is the main carrier for scavenged Al (Moran and Moore, 1988b;Stoffyn, 1979). Elevated bSiO 2 concentrations and associated high export rates of bSiO 2 were measured in the ENAB (up to 1.19 µM BSi) and in the IrB and LB (up to 4.27 and 4.63 µM bSiO 2 respectively) (Lemaitre et al, 2017). .…”
Section: Remineralization Versus Scavenging In the North Atlantic Andmentioning
confidence: 88%
“…The North Atlantic Drift region (NADR) is located between the NAST and the Reykjanes ridge, with higher nutrient concentrations than in the NAST (Longhurst, 1995). A strong bloom of coccolithophorids, with a maximum intensity in the Icelandic basin, occurred during the cruise, generating the highest primary production rate observed 85 on GEOVIDE (1740 molC.m -2 .d -1 , station #26, Fonseca-Batista et al, 2019) and high carbon export (up to 80 molC.m -2 .d -1 , station #32, Lemaitre et al, 2018). Four open ocean stations were sampled in this province: in the northern branch of the NAC (station #21), at the Subpolar front (station #26), in the northern branch of the NAC (station #32) and on the Reykjanes Ridge (station #38).…”
Section: Study Area: Hydrographical and Biogeochemical Contextmentioning
confidence: 95%
“…1. This figure also presents the main surface currents, as described in details (Zunino et al, 2017) and , together with the three main 70 biogeochemical provinces identified by Longhurst (1995) and described in details by Lemaitre et al (2018). The position of the stations where PREEs were sampled (Fig.…”
Section: Study Area: Hydrographical and Biogeochemical Contextmentioning
confidence: 95%
See 1 more Smart Citation
“…If this balance is positive for net organic matter production, as it is the case, the fate of these materials is either burial in the sediments or/and horizontal export to other ocean regions. Despite sinking particles representing the major contribution to the export of organic matter from the euphotic zone in the eSPNA (Giering et al, 2014;Martin et al, 2011), sinking particulate material suffers remineralization in the mesopelagic and bathypelagic waters before reaching the sediments (Alkire et al, 2012;Lemaitre et al, 2018). As a consequence, the burial of organic nitrogen in the sediments of the open ocean (0.20 kmol/s; Brunnegård et al, 2004) and shelves (1.2 kmol/s; Wollast, 1993) is one order of magnitude lower than the net nitrate uptake computed here, and the organic nitrogen budget is then dominated by lateral fluxes of DON.…”
Section: 1029/2018gl080284mentioning
confidence: 99%